Influence of pre-ignition pressure rise on safety characteristics of dusts and hybrid mixtures - Spitzer, Stefan H; Askar, Enis; Benke, Alexander; Janovský, Břetislav; Krause, Ulrich; Krietsch, Arne (Elsevier Science, 2022)
For the determination of the safety characteristics of dusts it is necessary to disperse the dust in the oxidating atmosphere (usually air). In the standard procedures for dusts this is realized by a partially evacuated explosion vessel (20L-sphere) in which the dust gets injected from a dust chamber pressurized with air. Shortly after that injection (60 ms) the dust cloud gets ignited under turbulent conditions, that are otherwise seen as almost ambient with 20 degrees C and about 1 bar (abs). While there has been a lot of research about the influence of the ignition delay time and the level of turbulence in the recent years little attention was paid to the pre-ignition pressure rise and the allowed variations in the standards. In the following work we showed that the allowed ranges for the pressures in the different dust standards influence the safety characteristics of dust alone severely. Even though hybrid mixtures are an emerging risk problem in an interconnected industry there is no standard for the determination of their safety characteristics. In this work it is shown that especially for the preparation of hybrid mixtures of flammable dust and gas the pressures after injection of the dust and the mixing procedure have a large influence on the composition of the tested mixtures and therefore on the safety characteristics. Considering both effects, wrong concentration of gas and wrong initial pressure, the discrepancy of safety characteristics from different facilities will be too big to applicable. The methods to overcome these weaknesses are also presented.
Vliv před-iniciačního nárůstu tlaku na bezpečnostní charakteristiky prachů a hybridních směsí
Keywords: hybrid mixtures; 20L-sphere; pre-ignition pressure rise; post-injection pressure drop; safety characteristics; mixing procedure; hybridní směsi; 20L-koule; nárůst tlaku před zapálením; pokles tlaku po vstřiku; bezpečnostní charakteristiky; postup míchání